PENGGUNAAN INTERNET UNTUK MENINGKATKAN MOTIVASI SISWA BELAJAR SEJARAH PADA MASA PANDEMI COVID 19 - Erma Talib (LPPM Universitas Muhammadiyah Bulukumba, 2022)
This study aims to determine the use of the internet as a source of history learning to increase the learning motivation of class XI History students at SMA Negeri 22 Makassar in the 2020 2021 academic year. This research was conducted at SMA Negeri 22 Makassar with the research subjects of class XI students. The research sample was carried out by proportional random sampling. The different variable in this study is the use of the internet as a learning resource, while the dependent variable is learning motivation. Data was collected through questionnaires and documentation. Data analysis through regression technique. The use of the internet as a learning resource is categorized as good enough, while students learning motivation is in the high category. From the results of the regression analysis, the value of Fcount equals 19.607 with a significance of 0.000 less than 0.05, which indicates that the use of the internet as a learning resource affects the learning motivation of students in class XI History of SMA Negeri 22 Makassar in the 2020 2021 academic year